Comparative Proteomics of Chloroplasts Envelopes from Bundle Sheath and Mesophyll Chloroplasts Reveals Novel Membrane Proteins with a Possible Role in C4-Related Metabolite Fluxes and Development - Manandhar-Shrestha, Kalpana; Tamot, Banita; Pratt, Evan P.; Saitie, Samuel M.; Braeutigam, Andrea; Weber, Andreas P.; Hoffmann-Benning, Susanne (Frontiers in Plant Science, 2013)
As the world population grows, our need for food increases drastically. Limited amounts of arable land lead to a competition between food and fuel crops, while changes in the global climate may impact future crop yields. Thus, a second “green revolution” will need a better understanding of the processes essential for plant growth and development. One approach toward the solution of this problem is to better understand regulatory and transport processes in C4 plants. C4 plants display an up to 10-fold higher apparent CO2 assimilation and higher yields while maintaining high water use efficiency. This requires differential regulation of mesophyll (M) and bundle sheath (BS) chloroplast development as well as higher metabolic fluxes of photosynthetic intermediates between cells and across chloroplast envelopes. While previous analyses of overall chloroplast membranes have yielded significant insight, our comparative proteomics approach using enriched BS and M chloroplast envelopes of Zea mays allowed us to identify 37 proteins of unknown function that have not been seen in these earlier studies. We identified 280 proteins, 84% of which are known/predicted to be present in chloroplasts (cp). 74% have a known or predicted membrane association. 21 membrane proteins were 2-15 times more abundant in BS cells, while 36 proteins were more abundant in M cp envelopes. These proteins could represent additional candidates of proteins essential for development or metabolite transport processes in C4 plants. RT-PCR confirmed differential expression of thirteen candidate genes. Cp association was confirmed using GFP labeling. Genes for a PIC-like protein and an ER-AP-like protein show an early transient increase in gene expression during the transition to light. In addition, PIC gene expression is increased in the immature part of the leaf and was lower in the fully developed parts of the leaf, suggesting a need for/incorporation of the protein during chloroplast development.